PENGUATAN KEMANDIRIAN ANAK BERBASIS SCAFFOLDING MELALUI MENDONGENG - Daryati , Melia Eka (Universitas Mataram, 2024)
Children's independence will be difficult to develop if there is no habituation, education, and supportive environment. This community service aims to strengthen children's independence through the scaffolding method implemented in storytelling activities. Scaffolding is a learning approach that allows children to develop abilities gradually with the help and guidance of a companion. The implementation of the community service was carried out at the Lab School Early Childhood Education which involved all students, parents, and teachers. The methods used include material development and direct practice with storytelling. Community service activities were carried out in several stages starting from teacher and parent training on storytelling techniques based on the principle of scaffolding, children were involved in storytelling sessions designed to develop independence, reflection and discussion activities were used to measure progress and provide feedback on children's independence. Data were collected through interviews, and content analysis from aspects of children's independence. The results of the study showed that children's independence has great potential to become a habit through scaffolding where children's independence in thinking and acting, improving communication skills, and strengthening relationships between children, teachers, and parents are more memorable to children when using the storytelling method. Active activities during storytelling that use music, movement, and positive narratives in educating children's independence so as to create a fun learning experience for children. The continuation of this community service activity will develop scaffolding content in the form of ebooks.